INFOGRAPHIC EFFECTIVENESS IN PROMOTING HEALTH FOR SMOKERS AMONG BATAM COMMUNITIES - Deli; Donny (UNIVERSITAS STEKOM, 2023)
The main goal of this study is to create and analyze effectiveness of poster about the dangers of smoking to people in the city of Batam. The people in the city of Batam who use Instagram is the subject of this study. Multimedia Development Life Cycle (MDLC) is the method used to develop the poster and the analysis is carried by quantitative approach. Stratified Random Sampling method is the technique used in the study to collect samples. Data dissemination was carried out by distributing online questionnaires through various social media platforms. The results obtained from distributing the questionnaires were from 111 respondents. Hypotheses analysis will be carried out using the linear regression test method with the help of the SPSS 25 software. The result of this study is Performance Expectance has no significant influence on Behavioral Intention. Meanwhile Effort Expectancy, Social Influence and Facilitating Condition has influence to Behavioral Intention. The study's findings are believed to be a resource and source of knowledge for readers and academics in the future.